Chronic exposure to TGFβ1 regulates myeloid cell inflammatory response in an IRF7‐dependent manner. (10th November 2014) - Cohen, Merav; Matcovitch, Orit; David, Eyal; Barnett‐Itzhaki, Zohar; Keren‐Shaul, Hadas; Blecher‐Gonen, Ronnie; Jaitin, Diego Adhemar; Sica, Antonio; Amit, Ido; Schwartz, Michal
Abstract Tissue microenvironment influences the function of resident and infiltrating myeloid‐derived cells. In the central nervous system (CNS), resident microglia and freshly recruited infiltrating monocyte‐derived macrophages (mo‐MΦ) display distinct activities under pathological conditions, yet little is known about the microenvironment‐derived molecular mechanism that regulates these differences. Here, we demonstrate that long exposure to transforming growth factor‐β1 (TGFβ1) impaired the ability of myeloid cells to acquire a resolving anti‐inflammatory phenotype. Using genome‐wide expression analysis and chromatin immunoprecipitation followed by next‐generation sequencing, we show that the capacity to undergo pro‐ to anti‐inflammatory (M1‐to‐M2) phenotype switch is controlled by the transcription factor interferon regulatory factor 7 (IRF7) that is down‐regulated by the TGFβ1 pathway. RNAi‐mediated perturbation of Irf7 inhibited the M1‐to‐M2 switch, while IFNβ1 (an IRF7 pathway activator) restored it. In vivo induction of Irf7 expression in microglia, following spinal cord injury, reduced their pro‐inflammatory activity. These results highlight the key role of tissue‐specific environmental factors in determining the fate of resident myeloid‐derived cells under both physiological and pathological conditions.